2016
DOI: 10.1039/c6cp04382h
|View full text |Cite
|
Sign up to set email alerts
|

Ice nucleation on nanotextured surfaces: the influence of surface fraction, pillar height and wetting states

Abstract: In this work, we address the nucleation behavior of a supercooled monatomic cylindrical water droplet on nanoscale textured surfaces using molecular dynamics simulations. The ice nucleation rate at 203 K on graphite based textured surfaces with nanoscale roughness is evaluated using the mean fast-passage time method. The simulation results show that the nucleation rate depends on the surface fraction as well as the wetting states. The nucleation rate enhances with increasing surface fraction for water in the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 57 publications
0
43
0
Order By: Relevance
“…Cao et al added nanoparticles into polymer composite substrates and obtained the superhydrophobic surface [155]. Metya et al investigated the ice nucleation of a supercooled cylindrical water droplet on nanotextured surfaces at 203 K with the Cassie-Baxter and Wenzel states using molecular dynamics simulations [156], as shown in Figure 16. On the one hand, ice nucleation rate was found to enhance with the increase in surface fraction in the Cassie-Baxter state, whereas the nucleation rate decreased for the Wenzel state with increasing surface fraction.…”
Section: Anti-icing Theorymentioning
confidence: 99%
“…Cao et al added nanoparticles into polymer composite substrates and obtained the superhydrophobic surface [155]. Metya et al investigated the ice nucleation of a supercooled cylindrical water droplet on nanotextured surfaces at 203 K with the Cassie-Baxter and Wenzel states using molecular dynamics simulations [156], as shown in Figure 16. On the one hand, ice nucleation rate was found to enhance with the increase in surface fraction in the Cassie-Baxter state, whereas the nucleation rate decreased for the Wenzel state with increasing surface fraction.…”
Section: Anti-icing Theorymentioning
confidence: 99%
“…Xu et al [26] have studied the nucleation of vapor on a V -shape surface by MDS and found the various angles of this V -type affected the state and nucleation rate of water droplets formed on the surface. Metya et al [27] have studied the nucleation of water on nanoscale textured surfaces using MDS and have illustrated the dependence of nucleation rate on surface fraction. Toxvaerd [28] have studied vapor condensation on a planar surface with various attraction forces using MDS and have found that nucleation is promoted in the presence of the surface.…”
Section: Introductionmentioning
confidence: 99%
“…There have also been systematic trend studies focused on understanding the connections between nucleation rate or temperature with the lattice constant of the substrate, surface hydrophilicity, hydroxyl group structure and symmetry, and surface flexibility [39][40][41][42][43][44][45][46][47] . Various other influential surface characteristics such as charge-distribution 48 or nanotexture 49 have also been explored.…”
mentioning
confidence: 99%